2021
DOI: 10.1038/s41598-021-93896-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cellular PpIX potentiates sonodynamic therapy in a mouse glioma stem cell-bearing glioma model by downregulating the Akt/NF-κB/MDR1 pathway

Abstract: Glioblastoma (GBM) has high mortality rates because of extreme therapeutic resistance. During surgical resection for GBM, 5-aminolevulinic acid (5-ALA)-induced protoporphyrin IX (PpIX) fluorescence is conventionally applied to distinguish GBM. However, surgical intervention is insufficient for high invasive GBM. Sonodynamic therapy (SDT) combined with low-intensity ultrasonication (US) and PpIX, as a sonosensitizer, is an emerging and promising approach, although its efficacy is limited. Based on our previous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Preliminary in vitro studies have revealed that many cancer cells are lysed by SDT treatment, though the rate of cell death is dependent on the cell line. Preliminary in vivo studies yield similar results, confirming that SDT can trigger apoptosis 5 . This protocol aims to describe effective techniques and parameters for the SDT treatment of rodent models with intracranially implanted GBM cells using a benchtop FUS research platform.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Preliminary in vitro studies have revealed that many cancer cells are lysed by SDT treatment, though the rate of cell death is dependent on the cell line. Preliminary in vivo studies yield similar results, confirming that SDT can trigger apoptosis 5 . This protocol aims to describe effective techniques and parameters for the SDT treatment of rodent models with intracranially implanted GBM cells using a benchtop FUS research platform.…”
Section: Introductionsupporting
confidence: 53%
“…Other sonosensitizers can be substituted and tested to determine the compound most suitable for efficacy and safety. Finally, treatment was commenced 3 h post 5-ALA injection, as previous literature has shown that this is the optimal time with that injection dosage 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, authors demonstrated that inhibition of the oncogenic Ras/MEK pathway restrained the efflux of PpIX due to ABCB1 level reduction in colon cancer cells. This was recently confirmed in a mouse malignant glioma where downregulation of MDR1 increased the cellular 5-ALA-induced PpIX level [ 43 ]. Researches on ABCB1 are very limited, hence its role remains to confirm.…”
Section: Heme Metabolism—a Complex Network Tightly Regulated By Enzym...mentioning
confidence: 69%
“…As just mentioned, SDT involves the application of focused ultrasound with a substance that sensitizes cells to the destroying effects of sound, called sonosensitizer. It includes both ultrasonication, via non-invasive lowintensity ultrasound penetrating soft tissues and focus on a speci c site, and sonosensitizers, which embrace nontoxic chemical agents such as 5-ALA, ATX-70, Hypocrellin, Rose Bengal and many others [64-66]; some of these compounds are commonly used in glioma surgery to intraoperatively visualize the tumor and can be employed to induce cytotoxic effects to neoplastic cells when subjected to a speci c acoustic eld [31,39,67]. The advantage of this technique is to minimize adverse events and maximizing on-target responses.…”
Section: Sonodynamic Therapymentioning
confidence: 99%